Faktor- Faktor Yang Mempengaruhi Kinerja UMKM Setelah Pandemi Covid 19 - Anim Wiyana, Marcelinus Yanto, Febrianus Akun, Wahyu Kurniawan Asgap, Muhammad Tafsir (STIE AMKOP, 2023)
The aim of this research is to find out whether the factors of human resource competency, financial literacy, use of Accounting Information Systems, product innovation, business capital, marketing access, e-commerce sales systems and social media adoption have on the performance of MSMEs after the Covid 19 pandemic among Micro, Small and Medium Enterprises(UMKM) business actors in Makassar city. The sample used in this research was 61 MSMEs with various types of business. The research method used is a quantitative method. The results of the questionnaire obtained by distributing it via Google Form have been tested for validity and reliability, and have been tested for classical assumptions in the form of normality assumptions, multicollinearity assumptions and heteroscedasticity assumptions. The data analysis method uses multiple linear regression techniques. Data were analyzed using the SPSS version 25 program. The results of this research show that the variables use of accounting information systems, business capital, and marketing access have a significant effect on the performance of MSMEs. Meanwhile, the variables of HR competency, financial literacy, product innovation, e-commerce sales system, and social media adoption do not have a significant effect on MSME performance. Keywords: accounting information system, business capital, marketing, human resources, financial literacy, product innovation, e-commerce, social media